A CRITICAL EXAMINATION OF LAND COST ELEMENTS ON PRIVATE HOUSING DEVELOPMENT IN AWORI LAND, OGUN STATE, NIGERIA. A CASE OF ADO/ODO-OTA LGA. - Atinuke Adebimpe, Orekan; Bamidele, Adeyemi; Ekott, Ubong John (International Journal of Property Sciences (E-ISSN: 2229-8568), 2021)
This study examines the cost elements associated with land acquisition and development and the effect it has on public housing development using Awori land in Ado/Odo-Ota LGA in Ogun state, Nigeria, as a case study. To achieve this, a survey was administered to estate surveyors & valuers and officers of the Bureau of Lands and Survey who are involved in property developments. The findings revealed that land registration cost, lease cost, deeds of assignment were ranked as important. It is also found that there is also a significant relationship between land cost elements and rate of housing development. The study further revealed that there is a positive relationship between the land cost elements and the rate of housing development. In conclusion, this implies that an increase in one of the land cost elements will affect housing development.